All Things Considered: Systematic Cognitive Processing and Electoral Decision-making - Barker, David C.; Hansen, Susan B. (The Journal of politics, 2005)
This paper seeks to understand what difference it makes if voters systematically consider a representative range of salient criteria before choosing a candidate, and whether the effects of such systematic processing are conditioned by political knowledge. To this end, we executed experiments during the 2000 electoral season that randomly exposed some subjects to an Analytic Hierarchy Processing (AHP) tool, which encourages systematic processing of various orthogonal decision criteria in complex choice environments. We predicted, and found, that the choices of knowledgeable voters exposed to AHP were weaker and less consistent than control group responses, suggesting that systematic processing induces integrative complexity and perhaps “analysis paralysis” among knowledgeable voters. However, we found that among less knowledgeable voters, the opposite pattern generally emerged—AHP exposure was associated with even greater reliance on party ID and ideology cues, perhaps even bolstering predispositions via projection and rationalization.